Pengaruh E-Government, Kapabilitas APIP dan Persentasi Penyelesaian Tindak Lanjut terhadap Opini Audit Laporan Keuangan Pemerintah Daerah di Indonesia - Indriyani Wulandari; Bandi Bandi (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2015)
Audit Opinion BPK is the result of the audit process in the form of a statement that can be a picture of the quality of financial statements of the government, so that it becomes a reference for the central government in the finance ministries in assessing performance achievement of local government in particular to provide rewards and punishments related to public financial management , In connection with these problems, this thesis aims to obtain empirical evidence about the influence of the existence of the implementation of E-Government, APIP capability, and the percentage of completion of the Follow-up BPK BPK audit opinion. The analysis used in this research is multiple regression analysis using the method of research is purposive sampling. This study uses secondary data IHPS BPK 2015, the data IACM 2013, the data Peggi Kemenkominfo RI 2016. Researchers analyzed 228 local government composed of local government districts and cities. The results showed that the existence of e-government implementation and follow-up Completion Percentage BPK significant impact positively on BPK audit opinion, while APIP capability does not have a significant influence on the BPK audit opinion. APIP is not influential capability to audit opinion because most local governments in Indonesia APIP its capability level remained at level 1 (Initial) so it has not been able to support the implementation of effective governance. Applications of this research in the future it is suggested that the local government, Inspectorate (APIP area), BPK RI to cooperate in creating a better audit opinion that WTP opinion on the financial statements.